2016
DOI: 10.1007/978-3-319-32213-1_11
|View full text |Cite
|
Sign up to set email alerts
|

PAT and Px Code Sidelobe Reduction Using Wavelet Neural Network

Abstract: Pulse compression is a significant aspect for improving the radar detection and range resolution. To improve the range detection, the pulse width is increased to overcome the transmitter maximum peak power limitations. However, pulse compression is accompanied with time sidelobes that can mask the small targets. The Wavelet Neural Network (WNN) is a new technique used for pulse compression sidelobe reduction. In this paper, Morlet function is applied as an activation function for WNN and the backpropagation (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Where ℎ and denotes the neurons number in the hidden and the input layer respectively. Morlet function is deployed in the hidden layer as an activation function, and sigmoid function is deployed in output layer [11]. Equation 17 below indicates the Morlet function, as displayed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where ℎ and denotes the neurons number in the hidden and the input layer respectively. Morlet function is deployed in the hidden layer as an activation function, and sigmoid function is deployed in output layer [11]. Equation 17 below indicates the Morlet function, as displayed in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Their results indicated that WNN has a powerful approximation capability and suitability in prediction and modeling. Therefore, WNN is a significant tool in classification and signals processing [11]- [12]. In this article, a new approach for classification of prostate cancer's risk is proposed using WNN.…”
mentioning
confidence: 99%